Contribution to the Turbulent Flow Separation Study in an Asymmetric Subsonic Plane Diffuser by RANS Models - M. Aounallah; O. Madani Fouatih; M. Belkadi; L. Adjlout (Algerian Journal of Research and Technology (AJRT), 2020)
The present study deals with separate turbulent flow in a 2D subsonic asymmetric plane diffuser using ANSYS Fluent commercial code. Several models of turbulence have been tested namely: the Spalart-Allmaras model, k-ω SST, feasible k-ε and RSM. The Spalart-Allmaras and k-ω SST models provided the best tuning for the 2D case. Instantaneous flow recirculation has been observed along the inclined wall where the average flow profile changes gradually as the flow enters the expansion zone. The structure of the flow in the asymmetric diffuser, as a function of the variation of the angles and according to different Reynolds numbers, was also analyzed. The results show that the influence of the size of the recirculation region for a turbulent flow is ambiguous with the variation of the Reynolds number, but evident with the change of angles of the diffuser.